Discovery, Optimization, and Biological Characterization of 2, 3, 6‐Trisubstituted Pyridine‐Containing M4 Positive Allosteric Modulators. (28th March 2019) - Schubert, Jeffrey W.; Harrison, Scott T.; Mulhearn, James; Gomez, Robert; Tynebor, Robert; Jones, Kristen; Bunda, Jaime; Hanney, Barbara; Wai, Jenny Miu‐Chen; Cox, Chris; McCauley, John A.; Sanders, John M.; et al.
Abstract: Herein we describe the discovery and optimization of a new series of 2, 3‐disubstituted and 2, 3, 6‐trisubstituted muscarinic acetylcholine receptor 4 (M4 ) positive allosteric modulators (PAMs). Iterative libraries enabled rapid exploration of one‐dimensional structure–activity relationships (SAR) and identification of potency‐enhancing heterocycle and N ‐alkyl pyrazole substituents. Further optimization led to identification of the potent, receptor‐subtype‐selective, brain‐penetrant tool compound24 (7‐[3‐[1‐[(1‐fluorocyclopentyl)methyl]pyrazol‐4‐yl]‐6‐methyl‐2‐pyridyl]‐3‐methoxycinnoline). It is efficacious in preclinical assays that are predictive of antipsychotic effects, producing dose‐dependent reversal of amphetamine‐induced hyperlocomotion in rats and mice, but not in M4 knockout mice. Cholinergic‐related adverse effects observed in rats treated with24 at unbound plasma concentrations more than 3‐fold higher than an efficacious dose in the hyperlocomotion assay were fewer and less severe than those observed in rats treated with the nonselective M4 agonist xanomeline, suggesting a receptor‐subtype‐selective PAM has the potential for an improved safety profile. Abstract : Novel series of M4 PAMs : Optimization of series of 2, 3‐di‐ and 2, 3, 6‐trisubstituted pyridines led to the potent, receptor‐subtype‐selective, brain‐penetrant positive allosteric modulator (PAM)24 with efficacy in rodent locomotor activity assays. Comparison of cholinergic adverse effects in rats treated separately with24 and the M4 agonist xanomeline suggests that a receptor‐subtype‐selective PAM offers the potential for an improved safety profile.